THE USE OF LIGHTWEIGHT AGGREGATE IN PREPARATION OF THERMAL INSULATION LIME-BASED RENDERS - Jaroslav Pokorný; Milena Pavlíková; Zbyšek Pavlík (Acta Polytechnica CTU Proceedings)
Lime-based renders are common part of historical or older buildings that don’t always provide a comfortable inside climate due to the problems with high thermal losses. Thermal insulation renders may possibly retrofit or replace original render layers and mitigate negative impacts of harmful external climate. In this respect, determination of basic structural, mechanical and thermal properties of lime-based renders containing various amount of perlite that was used as partial silica sand replacement is presented in the paper. Experimental tests performed for 28 days high relative humidity-cured samples showed significant decrease in bulk density and apparent density for renders with incorporated perlite compared to reference render mix composed of silica sand-based aggregate only. Accordingly, porosity of perlite mortars was significantly higher, what led to the lower thermal conductivity values in comparison with reference render. Although the mechanical resistance of perlite-modified renders was lower than that of reference material, it was still sufficient for their use as thermal insulation layer compatible with older construction materials. Based on the obtained data it can be concluded, the analysed hydrated lime-based plasters with perlite admixture can be considered as promising materials for buildings refurbishment.